2019
DOI: 10.1016/s2095-3119(18)61996-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and QTL mapping of Z550, a rice backcrossed inbred line with increased grains per panicle

Abstract: An elite backcrossed inbred line Z550 with increased grains per panicle was identified from advanced backcrosses between Nipponbare and Xihui 18 by simple sequence repeat (SSR) marker-assisted selection (MAS). Z550 carries 13 substitution segments distributed on chromosomes 1, 6, 7, 8, 9, 10, and 12, with an average substitution length of 1.68 Mb. Compared with the Nipponbare parental line, plant height, panicle length, spikelets per panicle, grains per panicle, and grain weight for Z550 were significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…qGP8 was also previously reported associated with seed germination under osmotic stress detected in the RM6208-RM8264 marker interval [38]. However, the same QTL was detected in linked marker RM7027 associated with the grain number per panicle [39]. These inferences support our study that the four QTLs are linked to seed germination and yield.…”
Section: Discussionsupporting
confidence: 90%
“…qGP8 was also previously reported associated with seed germination under osmotic stress detected in the RM6208-RM8264 marker interval [38]. However, the same QTL was detected in linked marker RM7027 associated with the grain number per panicle [39]. These inferences support our study that the four QTLs are linked to seed germination and yield.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, Pang et al (2017) and Feng et al (2018) reported QTLs in the population, generated by crossing Ils developed from local rice varieties. Similarly, QTLs were reported in the F 2 population derived from a cross between a back cross inbred line (japonica × indica) and a japonica cultivar Z550 (Wang et al, 2018). Various studies reported QTLs for yield traits in rice using primary mapping populations like F 2:3 (Sabouri et al, 2009;Zhang et al, 2010;Kim et al, 2014;Tian et al, 2015;Biswas et al, 2017;Kumar et al, 2019) and F 2:4 (Rabiei et al, 2015;Verma et al, 2017;Jeon et al, 2018;Kumar et al, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…There are many reports on mapping yield QTLs using wild species ( Swamy and Sarla, 2008 ; Swamy et al, 2011 , 2014 ; Wickneswari et al, 2012 ; Ma et al, 2016 ; Bhatia et al, 2018 ). Back cross inbred lines are useful for mapping QTLs and gene pyramiding ( Bhatia et al, 2018 ; Wang et al, 2018 ). In addition, QTL pyramiding using introgression lines (ILs) is an effective method in molecular breeding for complex traits ( Feng et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, pyramiding these elite QTLs by marker‐assisted selection will certainly benefit rice high‐yield breeding. Most QTL studies have involved indica / japonica populations in which a large variation in panicle size was observed (S. M. Wang et al, 2019; Xie et al, 2019; Zhang et al, 2021). Although a number of QTLs for panicle structure have been detected, a few QTL/gene have been cloned, such as MOC1 , LAX1 , LAX2 , GN1a/OsCKX2 , DEP1 , SP1 and APO1 (http://www.ricedata.cn/gene/).…”
Section: Introductionmentioning
confidence: 99%